PENGARUH CURRENT RATIO DEBT TO EQUITY RATIO DAN NET PROFIT MARGIN TERHADAP RETURN ON EQUITY PADA PERUSAHAAN PT PERTAMINA PERSERO TAHUN 2012 – 2022 - Kurniawan, Zen; Marjohan, Masno (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of the Current Ratio Debt to Equity Ratio and Net Profit Margin on Return on Equity at PT Pertamina (Persero) in 2012 - 2022, either partially or simultaneously. The method used is a quantitative method. The sample used is the financial report of PT Pertamina (Persero) for 11 years. The sampling technique uses a Non-Probability Sampling technique, namely; with a purposive sampling technique. The analysis in this research used the program, SPSS (Statistical Package for Social Science) software version 23.0. The research results on the Current Ratio variable (X1) do not have a significant effect on Return on Equity with the result t_count < t_tabel or -0.397 < 2.367 then the significant value of the Current Ratio variable is ρ value > Sig. 0.05 or 0.703 > 0.05. The variable Debt to Equity Ratio (X2) has a significant effect on Return on Equity with the result t_table < t_count or 3.027 > 2.367, with a significant value for the Debt to Equity Ratio variable of ρ value > Sig.0.05 or 0.019 < 0.05. The Net Profit Margin variable (X3) has a significant effect on Return on Equity (ROE) with the result t_table < t_count or 4,899 > 2,367, with a significant value for the Net Profit Margin variable of ρ value > Sig.0.05 or 0.02 > 0.05 Based on the Current Ratio Debt to Equity Ratio and Net Profit Margin have a significant effect on Return on Equity with the equation result F_count < F_tabel 13.311 > 4.46, this is also reinforced by ρ value < Sig.0.05 or 0.003 > 0.05